Spleen necrosis virus gag polyprotein is necessary for particle assembly and release but not for proteolytic processing. - Weaver, T A (1990)
The nature of spleen necrosis virus pol gene expression and the role of gag and gag-pol polyproteins in virion assembly was investigated. The DNA sequence of the gag-pol junction revealed that the two genes occupy the same open reading frame but are separated by an in-frame amber stop codon. Biochemical analysis of gag-pol translational readthrough in vitro and in Escherichia coli suggests that, in a manner similar to that in other mammalian type C retroviruses, amber stop codon suppression is required for pol gene expression. Removal of the gag stop codon had little or no effect on synthesis or cleavage of the polyprotein but interrupted particle assembly. This block could be overcome by complementation with wild-type gag protein.